13 Mucinous ovarian carcinoma: therapeutic options old and new. (18th September 2019) - Gorringe, K; Cheasley, D; Wakefield, M; Campbell, I; Antill, Y; Scott, C
Abstract : Objectives: Mucinous ovarian carcinoma (MOC) is a rare ovarian cancer subtype that responds poorly to conventional chemotherapy. Recurrent and advanced disease have poor survival and there are no specific guidelines for their treatment. We used a large cohort of genomic and immunohistochemical data to evaluate the likelihood of success of possible therapeutic interventions. Methods: We used DNA sequencing data (n=185) and genome-wide copy number (n=199) from primary MOC to identify key genetic events, homologous recombination deficiency scores and mismatch repair deficiency. Immunohistochemistry data was obtained for CK7, CK20, PAX8, p16, CDX2, HER2 and ER (n=162–256) and tumour infiltrating lymphocytes were counted on H&E stained slides (n=40). Results: Therapies exploiting homologous recombination deficiency are unlikely to be effective in MOC, as only 1.5% had a homologous recombination deficiency score of more than 50. Mismatch repair deficiency was very rare (<1%). Most cases had low lymphocytes counts, corresponding to a moderate mutation load. Events that suggest an existing targeted therapy include: ERBB2 amplification(26%), ERBB3 mutation(4%) and BRAF mutation(9%). Novel agents currently in clinical trials targeting genetic events such as TP53 missense mutation(46%), RNF43 mutation(11%), PIK3CA mutation(8%) and KRAS/NRAS mutations(66%). Conclusions: MOC is genetically diverse but with a number of potential targets. Importantly, the clinically observed lack of response to cisplatin is supported by a corresponding lack of a genomic signature, and MOC are unlikely to respond to PARP inhibitors. The role of immunotherapy is unclear. Testing novel therapeutic options in appropriate patient-derived models will be crucial and we are currently developing organoid cultures from this disease.